AD, Volume 29, n° 1, 2004: Full Issue - Full issue, (Africa Development, 2004)
Contents Introduction Lansana Keita ................................1 Modernité et interpretations religieuses Samir Amin .....................................7 On Prospective: Development and a Political Culture of Time Souleymane Bachir Diagne .........................55 Fanon and Development: A Philosophical Look Lewis Gordon .............................................71 Philosophie et politique: Pour une discussion avec Lansana Keita Paulin Hountondji .......................................95 African Development and the Primacy of Mental Decolonization Messay Kebede ......................................107 Philosophy and Development On the Problematic of African Development: A Diachronie Analysis Lansana Keita ........................................131 A Relevant Education for African Development - Some Epistemological Considerations Francis B. Nyamnjoh ...................................161 Book Review Amartya K. Sen, 2000, Development as Freedom (New York: Anchor Books, 366 + xvi pages) Lansana Keita ......................................185